Measuring Distance Learning System Adoption in a Greek University during the Pandemic Using the UTAUT Model, Trust in Government, Perceived University Efficiency and Coronavirus Fear - Konstantinos Antoniadis; Kostas Zafiropoulos; Dimitra Mitsiou (MDPI AG, 2022)
The COVID-19 pandemic has led most universities around the world using e-learning services as an alternative to their curricula. These distance learning tools can help universities expand and enhance their curricula with flexible learning techniques. In order to measure distance learning systems adoption in the University of Macedonia, a Greek university in the city of Thessaloniki, an extended version of the UTAUT model is introduced by using the constructs of Trust in Government regarding the management of the pandemic, Perceived University Efficiency on issues regarding distance learning provision and Corona Fear. To analyze the proposed model, an online survey of 471 university students was conducted. Data were analyzed using Partial Least Squares. The findings revealed that students' attitudes toward University Efficiency affect key variables of the proposed model, such as Performance Expectancy, Effort Expectancy, Social Influence, Facilitation Conditions and Use Behavior. Additionally, Trust in Government affects Perceived University Efficiency, and Use Behavior and Corona Fear affects University Efficiency and Trust in the Government in the management of pandemic issues. In contradiction with other research, Corona Fear has no moderating effects. University efficiency, Trust in Government and Corona Fear, because of the effects that they have on key variables, may have important managerial implications when considering the adoption of distance learning systems during the pandemic and in general.